ECONOMIC ASSESSMENT OF PRODUCTION RISKS IN INDUSTRIAL ENTERPRISES - Rahmatova M. G.; Gafurov Sh. N. (Modern American Journals, 2025)
This article describes the forms, types and causes of economic risks that can be observed in industrial enterprises, and some methods for their assessment are presented. It also provides general conclusions on the calculation of the economic losses that may arise for an industrial enterprise as a result of these economic risks, their impact on the further activities of the enterprise, and the effective economic compensation of these losses.
Keywords: Economic risk, economic losses, risk management, economic consequences, effective strategy, rational exploitation of resources, resource scarcity.